2018
DOI: 10.1016/j.ebiom.2018.10.072
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ maintains the metabolic heterogeneity and homeostasis of renal tubules

Abstract: BackgroundThe renal tubules, which have distant metabolic features and functions in different segments, reabsorb >99% of approximately 180 l of water and 25,000 mmol of Na + daily. Defective metabolism in renal tubules is involved in the pathobiology of kidney diseases. However, the mechanisms underlying the metabolic regulation in renal tubules remain to be defined.MethodsWe quantitatively compared the proteomes of the isolated proximal tubules (PT) and distal tubules (DT) from C57BL/6 mouse using tandem mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…Within the cortex we found the highest amount of pNrf2 in cells positive for the distal tubular cell/early collecting duct cell marker calbindin. This is in accordance with other publications localizing Nrf2, its mRNA or one of its targets, heme oxygenase 1 in the kidney [ 34 , 35 , 36 ]. When quantifying total Nrf2, a tendential increase was found.…”
Section: Discussionsupporting
confidence: 93%
“…Within the cortex we found the highest amount of pNrf2 in cells positive for the distal tubular cell/early collecting duct cell marker calbindin. This is in accordance with other publications localizing Nrf2, its mRNA or one of its targets, heme oxygenase 1 in the kidney [ 34 , 35 , 36 ]. When quantifying total Nrf2, a tendential increase was found.…”
Section: Discussionsupporting
confidence: 93%
“…All PPARs have been detected in rodent and human kidney, including glomeruli, medullary collecting duct, and pelvic urothelium. Renal proximal tubule expresses lipid metabolism-related enzymes that can upregulate transcriptional activity by sufficient expression of PPARc [68]. Kidney can process free fatty acids (FFAs), including reabsorption by proximal tubule and metabolism within mitochondria of proximal tubule [69].…”
Section: Pparγ In Renal Lipid Metabolismmentioning
confidence: 99%
“…However, importantly, reduced expression was abrogated by CWHM‐12 treatment. In addition to being a biomarker for CKD, several studies support a functional role for EGF signaling in kidney fibrosis (Kok, Falke, Goldschmeding, & Nguyen, ; Liu et al, ; Lyu et al, ). A recent study identified a metabolic switch from oxidative phosphorylation to glycolysis associated with tubulointerstitial fibrosis and progressive CKD in human kidneys (Lemos et al, ).…”
Section: Discussionmentioning
confidence: 99%